Asuinrakennusten korjaustarve 1990-luvulla - Nippala, Eero; Skogberg, Marja (Asuntotutkimuksia, ISSN 0781-3244, 1991)
Tiivistelmä (s. 3). - Referat (s. 4).
Keywords: perusparannus; ennusteet; matemaattiset mallit; saneeraus